Investigation of Nuclear Structure and Symmetry Energy of Some Nuclei - Wabdan, Ahmed A.; Majeed, Wasan Z. (Iraqi Journal of Science, 2026)
The symmetry energy accounts for the rise in nuclear matter's energy as the ratio of protons to neutrons deviates from equality. Using the Coherent Density Fluctuation Model (CDFM), the nuclear symmetry energy (S), neutrons pressure (Po), and asymmetric compressibility (ΔK) in argon isotopes were calculated. The in-depth study also investigates the correlation between the neutron skin thickness (ΔRn) and the properties of the nuclear symmetry energy's density dependence for Ar isotope chains. In addition, the significance of the neutron-proton asymmetry, the nuclear symmetry energy's mass dependency, and the neutron skin's thickness are investigated. Analysis of density-dependent nuclear symmetry energy characteristics reveals unique pathways taken by the nuclei of (A = 35–41) and nuclei (A = 29–34) of Ar isotope chains. It is evident from the result that the nuclear symmetry energies of Ar isotope chains (A = 29–41) and their neutron skin thickness have an approximately linear correlation. It is also observed that, for Ar isotope chains, the neutron skin thickness obtained agrees rather well with the experimental results.